Intersectional Approaches to Teaching about Privileges - Siliman, Shadia; Kearns, Katherine (Radical Teacher, 2020)
The ’privilege walk’ is a classroom activity at many colleges and universities deployed to create a visual, embodied, and concreterepresentation of students’ earned and unearned social advantages. In this article, we engage in a systematic reflection to interpret the privilege walk through an intersectional lens, and we elaborate on our concerns around the use of the activity. We claim thatthe privilege walk ultimately cultivates a two-dimensional, rather than an intersectional, understanding of privilege and oppression. We then offer alternativeswhich adapt the core concept of the privilege walk activity, adding intersectionality to its structure and learning outcomes in order to challengestudents to recognize their positionalities. We describe our own privilege walk adaptations and we reflect on our observations of the outcomes as well as opportunities for further consideration. Through this reflection, we invite colleagues to a pedagogical and interdisciplinary conversation about their alternatives to the privilege walk.